Serum MicroRNAs as Biomarkers of Sepsis and Resuscitation - Lorena Oteiza; Antonio Ferruelo; Nicolás Nín; Mario Arenillas; Marta de Paula; Rachele Pandolfi; Laura Moreno; Raquel Herrero; Paloma González-Rodríguez; Óscar Peñuelas; Francisco Pérez-Vizcaíno; José A. Lorente (Applied Sciences, 2021)
There is a lack of biomarkers of sepsis and the resuscitation status. Our objective was to prove that the serum expression of certain microribonucleic acids (miRNAs) is differentially regulated in sepsis and is sensitive to different resuscitation regimes. Anesthetized pigs (Sus scrofa domesticus) received no treatment (n = 15) or intravenous live E. coli (n = 24). The septic animals received 0.9% saline at 4 mL/kg/h (n = 8) (low resuscitation group (LoR)) or 10–17 mL/kg/h (high resuscitation group (HiR)) (n = 8 each group). Blood samples were obtained at the end of the experiment for measurement of seven different miRNAs (RT-qPCR, Qiagen, Hilden, Germany). The serum expression of miR-146a-5p and miR-34a-5p increased significantly in the septic group, and miR-146a-5p was significantly lower in the HiR group than in the LoR group. The toll-like receptor signaling pathway involving 22 target proteins was significantly (adjusted p = 3.87 × 10−4) regulated by these two microRNAs (KEGG). Highly significant (p value = 2.22 × 10−16) protein–protein interactions (STRING) were revealed for these 22 hits. MiR-146a-5p and miR-34a-5p were identified as biomarkers of sepsis, and miRNA146a-5p seemed to be a biomarker of the intensity of the resuscitation.